Earliest perissodactyls reveal large-scale dispersals during the PETM - Jérémy Tissier; Thierry Smith (Proceedings of the National Academy of Sciences, 2026)
Perissodactyls were a diverse order of mammals in the Northern Hemisphere during the Paleogene, but very few species remain today. They first appear during the Paleocene–Eocene Thermal Maximum (PETM; 56 Ma) on the three continents of the Northern Hemisphere. Because they lack modern diversity, the study of their evolutionary history remains difficult, relying almost exclusively on fossils. In addition, their origin and early diversification remain elusive since all main groups appear at the same time with several genera and are already diverse, contrary to other modern mammal orders. Here, we investigate the early evolution of perissodactyls by analyzing a new dataset focusing on early species to obtain a new expansive phylogeny. This new topology, in combination with new observations and comparisons demonstrates that several genera are synonymous, simplifying the evolutionary picture of early perissodactyls. We show that the number of genera was overestimated and should be significantly reevaluated. These results also highlight fast dispersals of two genera, Pliolophus and Cardiolophus , on the three Northern continents, reflecting that of other modern mammals. The phylogeny also supports a potential Indo-Pakistani origin of perissodactyls. In addition, this large-scale phylogeny shows that many species that were named as “ Hyracotherium ” in the past (or sometimes “ Eohippus ”, the “dawn-horse”) and considered as “horses”, are not actually closely related to horses (Hippomorpha), including Hyracotherium itself, but can be considered as basal perissodactyls.